The delegation of authority and its impact on decision making process with mediating role of employee performance in Dubai Police - Hassan Alhosani, Adnan Ali (2022)
Dubai has witnessed the growth of numbers in population and global visitors, which makes it necessary for the city to have an excellent police department to secure all citizens, residents and visitors. This is necessary for improving Dubai's security and financial condition and cementing the city's importance in the world. The main objective of this study is to examine the relationship between the delegation of authority, organizational functionality and decision-making process under the mediating effect of employee performance among the employees in Dubai police department UAE. A total of 380 employees were selected as the study sample using a multistage sampling method. Questionnaires were used in data collection and responses were analysed using partial least squares structural equation modeling (PLS-SEM) for data analysis. The results showed that the delegation of authority affects decision-making and employee’s performance among the target population. Moreover, delegation of authority helps the organisation in achieving the objectives with accordance to the imperative’s factors of organizational functionality of the organisation. The managers may focus on the employee performance, which is affecting the decision-making and affects the efficiency of the department as well. The results of this research contributed substantially to the current body of knowledge in the domain of delegation of authority in Arab context. The novelty of this study stem from the reality that the issues and problems of power delegation in Dubai police department was assessed in terms of decision-making process. From these results some recommendations are also suggested which are quite helpful especially, with regards to the latest global models of contemporary leadership and the latest approaches and methods of modern decision-making.